1992
DOI: 10.1038/ng0692-204
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a candidate gene for Norrie disease

Abstract: Previous analysis has refined the location of the gene for Norrie disease, a severe, X-linked, recessive neurodevelopmental disorder, to a yeast artificial chromosome subfragment of 160 kilobases (kb). This fragment was used to screen cDNA libraries from human fetal and adult retina. As a result, we have identified an evolutionarily conserved cDNA, which is expressed in fetal and adult brain and encodes a predicted protein of 133 amino acids. The cDNA detects genomic sequences which span a maximum of 50 kb, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(86 citation statements)
references
References 27 publications
0
86
0
Order By: Relevance
“…1) and a tertiary structure similar to that of TGF-b (Meitinger et al 1993). Mutations in Norrin cause Norrie disease Chen et al 1992;Meindl et al 1992), an X-linked disorder characterized by vascular abnormalities in the eye and blindness, often accompanied by progressive hearing loss and mental retardation (Berger 1998). …”
Section: Norrinmentioning
confidence: 99%
“…1) and a tertiary structure similar to that of TGF-b (Meitinger et al 1993). Mutations in Norrin cause Norrie disease Chen et al 1992;Meindl et al 1992), an X-linked disorder characterized by vascular abnormalities in the eye and blindness, often accompanied by progressive hearing loss and mental retardation (Berger 1998). …”
Section: Norrinmentioning
confidence: 99%
“…The carboxyl terminus of submaxillary mucin is formed by a 240-residue disulfide-rich domain, which has significant sequence identity with similar domains at the carboxyl terminus of human prepro-von Willebrand factor (3), frog integumentary mucin FIMB.1 (6), and human mucins secreted by different tissues, including MUC2, MUC5AC, 4 MUC5B, 5 and MUC6 6 (5,(7)(8)(9)(10). Moreover, the 11 half-cystines in a 133-residue protein (norrin) 7 associated with Norrie disease in humans (11,12) are conserved in the carboxyl-terminal disulfide-rich domains of human prepro-von Willebrand factor, porcine submaxillary mucin, and several human mucins (13). It has been shown that the disulfide-rich domain of prepro-von Willebrand factor (14), porcine submaxillary mucin (15), and norrin (16) forms interchain disulfide bonds between two polypeptide chains in these molecules.…”
mentioning
confidence: 99%
“…Norrin acts as a tissue-specific ligand for Frizzled 4 (Fz4) to help direct retinal vascular development (Xu et al, 2004). Mutations in Norrin result in Norrie Disease (Berger et al, 1992;Chen et al, 1992), in which retinal vascular development is incomplete resulting in large areas of avascular retina, neovascularization, scarring, and retinal detachment. Heterozygosity for mutations in Fz4, result in familial exudative vitreoretinopathy (FEVR) (Toomes et al, 2004), in which retinal vascular development is perturbed, but often not as severely as in Norrie disease, resulting in areas of avascular retina, neovascularization, and a spectrum that ranges from focal traction retinal detachments to severe detachments and blindness.…”
Section: Retinal Vascular Developmentmentioning
confidence: 99%